Unprecedented emergencies during radiofrequency ablation procedure: a case series - Chabungbam, Margaret; Singh, Akoijam Joy; Singh, Longjam Nilachandra; Choorapra, Sreejith; Opo, Tasso; Moirangthem, Monica; Devi, Khwairakpam Selina; Rasaily, Prashant Kami (International Journal of Advances in Medicine, 2021)
Radiofrequency ablation (RFA) of nerves is an upcoming intervention for relieving chronic musculoskeletal pain. However, being relatively new not much publications are available on emergencies during the procedure. 66 years old male, a case of Osteoarthritis knee, underwent RFA genicular nerve of right knee. Conventional RFA of Superolateral, Inferomedial, Superomedial genicular nerves were done under C- arm guidance. Thirty minutes after the procedure, we found a boggy swelling developing over his right knee. It was a hematoma developing on the superomedial aspect of the right kneecap most likely due to injury to Superomedial genicular vessels accompanying the nerve. 67 years old female planned for RFA genicular nerves of both knees under C arm guidance. During the intervention, she complained of numbness around face, and suddenly went into disoriented state with muscle twitching and bluish discoloration of lips. Medicine consultation diagnosed the incident as LA associated systemic toxicity. 57 years old female with chief complaints of pain in left hemiplegic shoulder pain for 6 months duration admitted for suprascapular nerve block. During the procedure patient goes into hypotensive bradycardic episode. 65 years old female admitted for Medial calcaneal block for right heel pain. 24 hours after the procedure she has aggravated pain of foot. RFA is considered as a non-invasive, OPD based procedure for effective pain relief but it is also important to understand such unprecedented emergencies that can happen.